Современное развитие роботической хирургии. - Мансуров Б. (KLINIK TADQIQOTLAR VA INNOVATSION TIBBIYOT, 2026)
The article examines current issues in robotic surgery. It analyzes various aspects of this medical field, its stages of development, and future prospects. Special attention is given to robotic surgery from the perspectives of patients and researchers utilizing this modern robotic medical equipment. The article explores both the advantages and disadvantages of this field from the standpoint of the government, the healthcare system, and end users—namely patients and medical professionals. An assessment is provided of the development of robotic applications in medical practice and the volume of work performed by robots using this innovative modern technology.